A bottom-up framework for assessing greenhouse gas emissions and mitigation potential in food systems - Kakai, L.F.; Noufa, C.K.; Sapkota, T.B.; Corbeels, M.; Choptiany, J.M.H. (International Institute of Tropical Agriculture, 2025)
Food systems are among the largest and most complex sources of global greenhouse gas (GHG) emissions, yet existing accounting approaches remain largely top-down, spatially coarse, and poorly suited to informing actionable mitigation strategies. National inventories typically rely on aggregated activity data and default emission factors, which obscure local heterogeneity, mask emission hotspots, and provide limited guidance for subnational planning and implementation. This gap is particularly critical in developing countries, where climate commitments under Nationally Determined Contributions (NDCs) increasingly require spatially explicit, context-sensitive, and operationally relevant evidence to guide investments and policy design. The bottom-up approach framework presents a comprehensive, scientifically grounded, and policy-relevant framework for quantifying GHG emissions and mitigation potential across food systems. The framework emphasizes spatially explicit, activity-based accounting that integrates localized biophysical conditions, management practices, and production data to generate robust and context-sensitive emission inventories. It is structured around modular components that guide users through system boundary definition, activity data compilation, emission quantification, spatial aggregation, baseline and business-as-usual (BAU) scenario construction, and mitigation scenario analysis. By linking fine-scale data to policy-relevant outputs, the framework enables the identification of emission hotspots, the evaluation of practice-specific mitigation options, and the design of targeted, subnational climate interventions. To enhance transparency and decision relevance, it embeds explicit uncertainty characterization consistent with IPCC good practice principles. Overall, this framework supports national reporting, subnational climate planning, and the development of credible, implementable mitigation pathways aligned with NDCs and long-term low-emission development strategies.